Rare dental peculiarities associated with the hypomyelinating leukoencephalopathy 4H syndrome/ADDH - Wolff, Anna; Koch, Martin Jean; Benzinger, Silke; Waes, Hubertus van; Wolf, Nicole I.; Boltshauser, Eugen; Luder, Hans Ulrich (Pediatric dentistry, 2010)
Purpose: 4H syndrome/ADDH, a disease of the cerebral white matter, seems to be associated with delayed tooth eruption and other dental abnormalities, which so far could not be assessed conclusively - mainly because patients were too young. The aim of this study was to characterize these abnormalities in a sample of patients old enough for a reliable assessment. Methods: Three children, all diagnosed with 4H syndrome/ADDH, were followed from approximately 4 to 10 years of age and examined clinically and radiographically. In one case, a histopathological analysis supplemented these records. Results: All 3 patients showed a generalized delay in eruption of the primary and permanent teeth, which culminated in complete retention of all primary maxillary central incisors. Permanent mandibular second premolars were missing in all children and permanent maxillary central incisors of 2 individuals exhibited a concave labial surface, while agenesis of the permanent maxillary lateral incisors and natal or neonatal teeth were observed in one patient. Conclusion: 4H syndrome/ADDH seems to be associated with a delay in primary tooth eruption, complete retention of the primary maxillary central incisors, and shape abnormalities of the permanent maxillary central incisors, which otherwise are very rare. Therefore, a neurological examination would appear warranted when these peculiarities are encountered.